Complete genome sequencing and comparative genomic analysis of three donkey Streptococcus equi subsp. equi isolates - Zhang, Yuwei; Lv, FenFen; Su, Yan; Zhang, Huan; Zhang, Baojiang (Frontiers in Microbiology, 2023)
Streptococcus equi subspecies equi (S. equi) is the causative agent of strangles, which is one of the most common and highly contagious respiratory infectious illnesses in horses.Streptococcus equi (S. equi) is a horse-specific pathogen that originated from the closely related zoonotic pathogen Streptococcus equi subspecies zooepidemicus (S. zooepidemicus). Despite decades of research, the movement of genetic material across host-restricted diseases remains a mystery. Three S. equi donkey isolates (HTP133, HTP232, and HT1112) were recently isolated from a strangles epidemic on donkey farms in China's Xinjiang Province. In this study, we performed a comprehensive comparative analysis of these isolates using whole genome sequencing and compared them to the published genomic sequences of equine strain S. equi 4047 to uncover evidence of genetic events that shaped the evolution of these donkey S. equi isolates' genomes.Whole genome sequencing indicated that both strains were closely related, with comparable gene compositions and a high rate of shared core genomes .Our comparative genomic study indicated that the genome structure is substantially conserved across three donkey strains; however, there are several rearrangements and inversions when compared to the horse isolate S. equi 4047. The virulence factors conveyed by genomic islands and prophages, in particular, played a key role in shaping the pathogenic capacity and genetic diversity of these S. equi strains. Furthermore, we discovered that the HT133 isolate had a strong colonization ability and increased motility; the HT1112 isolates had a significantly higher ability for antimicrobial resistance and biofilm formation, and the HT232 isolate gained pathogenic specialization by acquiring a bacteriophage encoding hyaluronate lyase. In summary, our findings show that genetic exchange across S. equi strains influences the development of the donkey S. equi genome, offering important genetic insights for future epidemiological studies of S. equi infection.